1998
DOI: 10.1111/j.1532-950x.1998.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Evaluation and Assessment of the Accuracy of Reduction of Two Methods of Acetabular Osteotomy Fixation in Dogs

Abstract: These findings support the use of the SWP technique as an alternative method of acetabular fracture repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
1
24

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 9 publications
2
44
1
24
Order By: Relevance
“…However, the tests performed by other authors (Stubbs et al, 1998;Fitzpatrick et al, 2008;Bruce et al, 2014) yielded lower results, which can be explained by the use of synthetic bones in this study. The density of polyurethane lower than that of natural bone (O'Neill et al, 2012) and, therefore, the displacement results are lower when animal bones are used.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…However, the tests performed by other authors (Stubbs et al, 1998;Fitzpatrick et al, 2008;Bruce et al, 2014) yielded lower results, which can be explained by the use of synthetic bones in this study. The density of polyurethane lower than that of natural bone (O'Neill et al, 2012) and, therefore, the displacement results are lower when animal bones are used.…”
Section: Discussioncontrasting
confidence: 64%
“…After the bending test, all specimens of group 2 displayed a breakdown of the PMM above the fracture site. Likewise, Stubbs et al (1998) reported the same results for the stabilization of the acetabulum using the same technique. Considering that the major complication of iliac fracture stabilization is the loosening of the screws, the PMM used around the screws worked as a locking system, thus preventing this complication (Burton, 2011).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Implant failure can lead to malalignment of the fracture, osteoarthritis, and poor function. Because of technical difficulties associated with accuracy of reduction and complications with plating techniques, other methods of internal fixation have been used, including a tension‐band technique with screws and wire and strengthened with polymethylmethacrylate 11–13 …”
mentioning
confidence: 99%